Therapeutic effect of ofatumumab in patients with myasthenia gravis: immunoregulation of follicular T helper cells and T helper type 17 cells - Li, Shasha; Zhang, Zhaoxu; Liu, Zunjing (Frontiers in Neurology, 2023)
Introduction This study aimed to study the therapeutic effects of ofatumumab in patients with myasthenia gravis (MG) in addition to the immunomodulatory effects on peripheral follicular T helper (Tfh) cells and T helper type 17 (Th17) cells. Methods Thirty-one patients with anti-acetylcholine receptor (AChR) antibody-positive MG were included in this study. At weeks 0, 1, 2, and 4, an initial dose of 20 mg of ofatumumab was injected subcutaneously, with a 2-month follow-up after completing this first cycle. At baseline, 1 month, and 3 months, we assessed the Quantitative MG (QMG), 15-item MG-Quality of Life (MG-QOL15), and MG-Activities of Daily Living (MG-ADL) scales and measured the frequencies of Tfh, Th17, and B cells and the levels of anti-AChR antibody, IL-6, IL-21, and IL-17 in the peripheral blood. Results At 1 month and 3 months, the QMG, MG-QOL15, and MG-ADL scores were all significantly reduced. At 3 months, doses of prednisone were reduced by an average of 37%. Decreased frequencies of Tfh and Th17 cells, depletion of B cells, and reduced levels of IL-6, IL-21, and IL-17 were all observed at 1 month or 3 months. Discussion Therefore, the therapeutic effect of ofatumumab could be detected after one cycle of treatment, which was maintained for 2 months. The immunomodulatory effect of ofatumumab during the observation period may involve depletion of B cells, reduction of Tfh and Th17 cells frequencies, and reduced levels of IL-6, IL-21, and IL-17. The findings provide novel data for the potential application of ofatumumab in MG.